Promising Approaches to Optimize the Biological Properties of the Antimicrobial Peptide Esculentin-1a(1–21)NH2: Amino Acids Substitution and Conjugation to Nanoparticles - Casciaro, Bruno; Cappiello, Floriana; Cacciafesta, Mauro; Mangoni, Maria Luisa (Frontiers in Chemistry, 2017)
Antimicrobial peptides (AMPs) represent an interesting class of molecules with expanding biological properties which make them a viable alternative for the development of future antibiotic drugs. However, for this purpose, some limitations must be overcome: (i) the poor biostability due to enzymatic degradation; (ii) the cytotoxicity at concentrations slightly higher than the therapeutic dosages; and (iii) the inefficient delivery to the target site at effective concentrations. Recently, a derivative of the frog skin esculentin-1a, named esculentin-1a(1-21)NH2, [Esc(1-21): GIFSKLAGKKIKNLLISGLKG-NH2] has been found to have a potent activity against the Gram-negative bacterium Pseudomonas aeruginosa, a slightly weaker activity against Gram-positive bacteria and interesting immunomodulatory properties. With the aim to optimize the antimicrobial features of Esc(1-21) and to circumvent the limitations described above, two different approaches were followed: (i) substitutions by non-coded amino acids, i.e. α-aminoisobutyric acid or D-amino acids; and (ii) peptide conjugation to gold nanoparticles. In this mini-review, we summarized the structural and functional properties of the resulting Esc(1-21)-derived compounds. Overall, our data may assist researchers in the rational design and optimization of AMPs for the development of future drugs to fight the worldwide problem of antibiotic resistance.